AB0576 The frequency of autoimmune thyroid disorders in patients with psoriatic arthritis and the effect of anti tnf-alpha treatment on autoimmune thyroid disease. (23rd January 2014) - Tarhan, E. F.; Oruk, G. G.; Karaoǧullarından, U.; Can, G.
Abstract : Background: Psoriatic Arthritis (PsA)is an inflammatory rheumatic disease accompanied by psoriasis. Coexistence of autoimmune thyroid disorders and rheumatic diseases such as Sjögren's syndrome, systemic lupus erythematosus and rheumatoid arthritis has been shown in many studies. Objectives: In this study, the frequency of thyroid disorders in PsA patients and the effect of anti TNF-α treatment on autoimmune thyroid disease were investigated. Methods: Thyroid stimulating hormone, triiodothyronine, thyroxine, antithyroglobulin(Tg) and anti-thyroid peroxidase (TPO) of 95 patients followed at the rheumatology outpatient clinic were retrospectively evaluated. Sixty-six patients with PsA (F/M: 43/23) whose data were complete, and 35 healthy controls (F/M: 25/10) were included in the study. Thyroid ultrasonography was applied to all cases by an endocrinology specialist. Results: 38 of the PsA patients received disease modifying antirheumatic drugs (DMARDs) (Group 1; mean age: 43.94±9.81), and 28 anti TNF-α treatment (Group 2; mean age:42.25±11.48). Group 3 was comprised of healthy controls (mean age: 40.52±8.34). Significant differences were observed (p<0.05) between the mean anti-TPO values (121.35±1.13; 38.25± 15.88) and anti-Tg values (68.48±8.35; 27.33±1.48) of groups 1 and 2 (p<0.05). Similarly, significant differences were established (p<0.05) between mean anti-TPO values (121.35±1.13; 51.94±33.55) and anti-Tg values (68.48±8.35; 37.62± 2.12) of groups 1 and 3 (p<0.05). There were significant differences (p<0.05) between the mean anti-TPO values (38.25±15.88; 51.94±33.55) and anti-Tg values (27.33±1.48; 37.62± 2.12) of groups 2 and 3 (p<0.05). Thyroid nodules were observed in 20 patients in group 1, 5 patients in group 2 and 3 cases in group 3. Subclinical hypothyroidism in 1 patient, subclinical hyperthyroidism in 1 patient and clinical hypothyroidism in 1 patient were discovered in group 1. There was 1 patient with subclinical hypothyroidism and 1 with clinical hypothyroidism in group 2. In group 3, only 1 patient with subclinical hypothyroidism was identified. Conclusions: As a result, autoimmune thyroid disorders were observed more frequently in patients with PsA than in the control group. The PsA patients who are receiving DMARDs appeared to have autoimmune thyroid disorders more frequently than those receiving anti TNF-α treatment. This condition may be resulting from TNF-α on the pathogenesis of thyroid disorders. Further studies are needed to clarify this effect. Disclosure of Interest: None Declared